FLIP-FLOP LIGHTS FOR MARINE SAFETY (LAMPU FLIP-FLOP UNTUK KEAMANAN LAUT) - Fuadaturrahmah Fuadaturrahmah; Indri Dayana (PASCAL (Journal of Physics and Science Learning), 2022)
A flip-flop lamp has been created for sea safety, so as to minimize ship accidents, which means guaranteed sea security, protecting the marine ecosystem and maintaining sea cleanliness. The working principle of the flip-flop lamp is based on the concept of Ohm's law, Archimedes's law, and hydrostatic pressure. The time obtained to float the flip-flop lamp is 0.779 s, with a hydrostatic pressure of 2000 N / m, Flip-flop lights made for marine safety can float in water. From the data it can be that the 2000 N / m2 hydrostatic pressure takes 0.779 s, which means the tool can float completely in water because itdoes not take up to 1 second. this means it is ready to use at sea